A critical analysis of the South African Disaster Management Act and Policy Framework. Issue 4 (October 2014) - van Niekerk, Dewald
<x xml:space="preserve">Abstract</x> The promulgation of the South African Disaster Management Act No. 57 of 2002 and the National Disaster Management Policy Framework of 2005 placed South Africa at the international forefront by integrating disaster risk reduction into all spheres of government through a decentralised approach. Yet, good policy and legislation do not necessarily translate into good practice. This paper provides a critical analysis of the Act and Policy Framework. Using qualitative research methods, it analyses the attitudes and perceptions of senior public officials on all levels of government, the private sector and academia. The study finds that one of the weakest aspects of the Act and Framework is the absence of clear guidance to local municipalities. The placement of the disaster risk management function on all tiers of government remains problematic, funding is inadequate and overall knowledge and capacities for disaster risk reduction are insufficient.